Nitrogen and sulfur Co-doped graphene inlaid with cobalt clusters for efficient oxygen reduction reaction. (December 2018) - Yang, Hong Bin; Guo, Chunxian; Zhang, Liping; Hu, Fang Xin; Cai, Weizheng; Gao, Jiajian; Li, Chang Ming; Liu, Bin
Abstract: Cobalt based catalysts are promising for oxygen reduction reaction (ORR) for unitized regenerative fuel cells and alkaline metal-air batteries. Herein, we report a novel non-precious ORR catalyst, in which cobalt clusters with a mean size of ∼2 nm are inlaid into porous nitrogen and sulfur co-doped graphene matrix. Benefiting from the unique structural property of Co clusters and the three-dimensional (3D) hierarchical porous architecture of nitrogen and sulfur codoped graphene, the prepared catalyst exhibits excellent ORR catalytic activity with good methanol tolerance and long-term durability in alkaline environment. Graphical abstract: Nitrogen and sulfur co-doped graphene inlaid with cobalt clusters provides abundant accessible Co-Nx -C catalytically active sites, rapid charge transport and fast reactant/product diffusion for efficient oxygen reduction reaction. Highlights: Cobalt clusters catalyst, which with a mean size of ∼2 nm are inlaid into porous nitrogen and sulfur co-doped graphene matrix was developed. The unique structure of Co clusters inlaid nitrogen and sulfur co-doped graphene catalyst provides abundant Co-Nx catalytically active sites. The unique structure of Co clusters provides rapid charge transport and fast reactant/product diffusion for electrochemical reactions.